Diagnóstico qualitativo e exploratório dos sistemas de controle de inspeção do setor frigorífico - Oliveira, Jacqueline Felipe Carvalho de (2021)
Quality in the meatpacking industry gains greater notability in the global economy due to two joint actions, the legal requirements for imports and the implementation of federal and state program legislation, in addition to greater demand and rigor on the part of consumers. The processing, as well as the commercialization of meat products, follows specific legislation depending on the scope of its market, thus, this research aims to evaluate the quality management and its tools in order to understand its applicability in food industries of animal origin. The methodology used for the development of this work was based on a qualitative approach with bibliographic survey in databases of the Ministry of Agriculture, Livestock and Supply (MAPA), Municipal Inspection Service (SIM), State Inspection Service (SIE), Agency of Agricultural Defense of Paraná (ADAPAR), Animal Products Inspection Management (GIPOA), Animal Products Inspection Department (DIPOA) and finally Federal Inspection Service (SIF), by direct contact with competent managers and by scientific literature. Among the tools available to the food industries of animal origin, the selfcontrol programs established by Circular n. 175 (MAPA), RDC No. 275 (ANVISA), Decree No. 9,013 (DIPOA), Law No. 1283 (SIF), are procedures that meet the food safety and safety conditions required by legislation, as they are based on systematic continuous inspections of all factors that can interfere in any way with the quality of products exposed to consumption by the population. Thus, it is intended that the application and understanding of quality management and management tools, as well as guidance on the documents required by each institution, help companies in the meat industry in the complete adequacy of their products, involving their validation, safety and quality and, consequently, achieving credibility by competing with internal and external markets with special attention to its employees and final consumer. The exploratory research indicated that the large number of documents required makes it difficult to pursue the legalization of the processing and marketing products, however, the technology and systematization of inspection systems, guiding and virtually making documents available, promotes agility and efficiency to the manage voluminous data and information.